2007
DOI: 10.1111/j.1365-4632.2007.02880.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Japanese cases of lichen planus pigmentosus‐inversus

Abstract: Case 1 was a 51-year-old Japanese woman. She presented with an asymptomatic brown macule located on the right axilla of 2 months' duration. The smooth macule was 2 cm in diameter with a sharp demarcation (Fig. 1A). Case 2 was a 62-year-old Japanese man. He presented with asymptomatic, symmetric, gray-brown macules located on the groin, axillae, and popliteal region of 6 months' duration. The smooth macules were several millimeters to centimeters in diameter and sharply demarcated (Fig. 1B). Oral or nail lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 12 publications
4
60
1
1
Order By: Relevance
“…[1] However, Kashima et al, have described two Japanese patients with the disease. [3] We found only one report of lichen planus pigmentosus inversus in a phototype IV woman [4] and did not find previous reports of the disease in North African dark-skinned persons like our patients. Clinically, the condition is characterized by well-circumscribed violaceous-brown macules confined to intertriginous areas [1] It affects mainly the axillae and groin.…”
Section: Casementioning
confidence: 73%
See 1 more Smart Citation
“…[1] However, Kashima et al, have described two Japanese patients with the disease. [3] We found only one report of lichen planus pigmentosus inversus in a phototype IV woman [4] and did not find previous reports of the disease in North African dark-skinned persons like our patients. Clinically, the condition is characterized by well-circumscribed violaceous-brown macules confined to intertriginous areas [1] It affects mainly the axillae and groin.…”
Section: Casementioning
confidence: 73%
“…[1][2][3][4][5] In our series, all patients were women. The mean duration of symptoms before the diagnosis ranges from 2 months to 15 years.…”
Section: Casementioning
confidence: 96%
“…The treatment of LPP-inversus is unknown. Some authors reported that the lesions gradually disappeared without medication within several months 3 . The paraneoplastic nature of LPP was described previously 12 .…”
Section: Discussionmentioning
confidence: 99%
“…We now report a rare case of LPP-inversus in a 31-year-old woman. As far as we know, 17 cases have been reported in the world literature [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Zosteriform LP follows dermatomal lines and is thought to be an isotopic response to herpes zoster or at least showing antigens against varicella zoster virus in lesional skin [16,17,18]. Lichen planus pigmentosus-inversus is suggested to be a rare variant of LP limited to intertriginous regions and seems to have a short inflammatory phase with fast transformation into a long noninflammatory regressive phase with brown, nonpruritic, small inflammatory macules; scaling is limited [19,20,21,22,23,24,25]. Only one case of coexistence of classic LP and lichen planus pigmentosus-inversus has been described [26].…”
Section: Discussionmentioning
confidence: 99%